Voter Participation in the 2024 General Election in North Bolaang Mongondow Regency - Posangi, Rizki; Lahaling, Hijrah; Nusa, Apriyanto (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
General Elections (Pemilu) are the main pillar in a democratic system, where voter participation is an important indicator of the legitimacy and success of the election. North Bolaang Mongondow Regency as one of the regions in North Sulawesi Province has its own social and geographical characteristics that influence the dynamics of voter participation. This study aims to analyze the level of community participation in the 2024 Election and identify factors that encourage and inhibit such participation. The research method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation studies. The results of the study show that voter participation in this area has increased compared to the previous Election, although there are still challenges such as low political literacy, limited information distribution, and the strong influence of local figures. These findings provide an important overview for election organizers and policy makers to design more effective participatory strategies in the future.